Abdominal Ultrasound Does Not Reveal Significant Alterations in Patients With Nonceliac Wheat Sensitivity. Issue 1 (January 2019) - Soresi, Maurizio; Mansueto, Pasquale; Terranova, Antonino; D'Alcamo, Alberto; La Blasca, Francesco; Cavataio, Francesca; Iacobucci, Rosario; Carroccio, Antonio
Abstract : Goals: The goal of this study was (A) to evaluate abdominal ultrasound signs in nonceliac wheat sensitivity (NCWS) patients for features useful in diagnosis and (B) to compare these aspects with those of celiac patients to assess whether ultrasound can be useful in the differential diagnosis between NCWS and celiac disease (CD). Background: NCWS diagnosis is difficult as no biomarkers of this condition have as yet been identified. In CD ultrasound aspects have been identified that have a good diagnostic accuracy. Study: We prospectively recruited 45 NCWS patients (11 males, 34 females; mean age 35.7 y). Three control groups were included: (A) 99 age-matched CD patients; (B) 18 patients with seronegative CD; (C) 50 patients with irritable bowel syndrome (IBS) who did not improve on a wheat-free diet. NCWS diagnosis was confirmed on the basis of an elimination diet and double-blind placebo-controlled (DBPC) challenge. Ultrasound sign investigation included: dilatation of the small bowel loops, thickening of the small bowel wall, hyperperistalsis, enlarged mesenteric lymph nodes, ascites, hyposplenism, altered diameter of the portal vein. Results: NCWS patients showed a low frequency of pathologic ultrasound findings. Dilated or thickened loops appeared more often in CD patients than in NCWS patients (88.8% vs. 20%; P <0.0001). These US signs were significantly more frequent in seronegative CD than in NCWS patients (both P <0.0001), whereas no difference was found between NCWS patients and IBS controls. Conclusions: In NCWS patients' ultrasound does not show a characteristic pattern which could be helpful for diagnosis. However, US can be useful to differentiate between NCWS and CD patients and especially those with seronegative CD. (ClinicalTrials.gov NCT03017274).